Tellurite glasses handbook : physical properties and data - El-Mallawany, Raouf A. H. (Taylor & Francis, 2011)
"This handbook discusses the physical constants and properties of the unique, non-crystalline solids known as tellurite glasses. It includes rigid data from experiments conducted over the last 60 years and presents their elastic, anelastic, optical, electrical, and thermal properties. This second edition covers advances in development and applications such as new photonics, sensing, and optics applications. It includes new glass forming systems, thermal, elastic, relaxation, electrical, and optical properties, together with new current and potential applications, including nanocomposites, optical devices and fibers, photonics, and communication"--